Role of the casein kinase I isoform, Hrr25, and the cell cycle-regulatory transcription factor, SBF, in the transcriptional response to DNA damage in Saccharomyces cerevisiae - Ho, Yuen (The National Academy of Sciences of the USA, 1997)
In the budding yeast, Saccharomyces cerevisiae, DNA damage or ribonucleotide depletion causes the transcriptional induction of an array of genes with known or putative roles in DNA repair. The ATM-like kinase, Mec1, and the serine/threonine protein kinases, Rad53 and Dun1, are required for this transcriptional response. In this paper, we provide evidence suggesting that another kinase, Hrr25, is also involved in the transcriptional response to DNA damage through its interaction with the transcription factor, Swi6. The Swi6 protein interacts with Swi4 to form the SBF complex and with Mbp1 to form the MBF complex. SBF and MBF are required for the G(1)-specific expression of G(1) cyclins and genes required for S-phase. We show that Swi6 associates with and is phosphorylated by Hrr25 in vitro. We find that swi4, swi6, and hrr25 mutants, but not mbp1 mutants, are sensitive to hydroxyurea and the DNA-damaging agent methyl methanesulfonate and are defective in the transcriptional induction of a subset of DNA damage-inducible genes. Both the sensitivity of swi6 mutants to methyl methanesulfonate and hydroxyurea and the transcriptional defect of hrr25 mutants are rescued by overexpression of SWI4, implicating the SBF complex in the Hrr25/Swi6-dependent response to DNA damage.